Peran Program Pemberdayaan dalam Mengelola Lahan Kosong sebagai Sumber Tanaman Obat di Pedesaan - Rivaldo Armada Putra; Rindi Metalisa; Gilang Vabio; Muhammad Iqbal; Nur Hikmah; Nurfiza Nurfiza; Azzahra Annida Putri; Nadila Zulfa; Rara Mulyunika; Ranisha Armellia; Sela Selfia Ag (Jurnal Kabar Masyarakat, 2024)
The environment plays an important role for humans to meet their needs. Especially in meeting the needs of human endurance using traditional medicine. Medicinal plants have many types and have different properties. In the processing of medicinal plants, skills are needed so that the processed medicine has good quality and has few side effects compared to modern medicine. Many people in Sungai Batang Village are also affected by Dengue Fever (DBD). Therefore, it is necessary to cultivate medicinal plants in the Sungai Batang Village area to prevent the continuation of various diseases that will attack the health of the people of Sungai Batang Village. In maintaining the stability of public health in Sungai Batang Village, residents, especially farmer groups and village youth, participate in the cultivation of these medicinal plants and can maintain the medicinal plants to grow.